Application of artificial intelligence in 6G internet of things communication in interactive installation art. (14th July 2022) - Wang, Xiaolong; Cai, Ling
The study aims to further analyse the application of intelligent Internet of things (IoT) technology and Artificial Intelligence (AI) technology in the art field, and promote the intelligent development of the art field. The study explores the application of AI technology in art management and art exhibition in the era of IoT, designs the intelligent management system of IoT art exhibits, and discusses the practical application effect of the system. It is found that there is excellent application effect of the art management system, and the shortest response time of the system is only 0.379 seconds, which can meet the actual application of the museum. Meanwhile, the multi-touch system based on BP Neural Network (BPNN) technology is designed, and BPNN is optimised. The results suggest that the multi-touch system has the highest gesture recognition accuracy of 99.4%, which is better than Hidden Markov Models (HMM). The results can provide theoretical support and reference for the development and research of intelligent IoT technology in the field of interactive art.